Review of diagnostic methods and results for HIV‐associated disseminated histoplasmosis: Pathologists are not sufficiently involved. Issue 11 (2nd September 2021) - Nacher, Mathieu; Valdes, Audrey; Adenis, Antoine; Blaizot, Romain; Ugo, Françoise; Abboud, Philippe; Demar, Magalie; Djossou, Félix; Epelboin, Loïc; Misslin, Caroline; Blanchet, Denis; Couppié, Pierre; et al.
Abstract: Objectives: Disseminated histoplasmosis is a major killer of HIV‐infected persons in Latin America. Antigen detection, fungal culture and Polymerase Chain Reaction are often not available, but cytology and histology are present in most hospitals and may offer a diagnostic alternative. In this study, we review 34 years of clinical experience to describe the roles of cytology and histology in diagnosing disseminated histoplasmosis. Methods: Retrospective multicentric study of 349 patients between 1 January 1981 and 1 October 2014 with confirmed disseminated histoplasmosis. Results: Around 32/214 (14.9%) of samples were screened using cytopathology, as were 10/101 (9.9%) bronchoalveolar lavage samples and 5/61 (8.2%) of spinal fluid samples. The samples most commonly sent to pathology were liver biopsies, lower digestive tract and lymphnode biopsies; the greatest proportion of positive results were found in lower digestive tract (43/59 (72.9%) positives), lymph node (39/63 (66.1%)), and liver (38/75 (50.7%)) samples. Overall, 97.2% of bone marrow and 97% of bronchoalveolar lavage samples were directly examined by a mycologist. Positive direct examination was independently associated with death (aHR = 1.5 (95%CI = 1–2.2)). Conclusions: Opportunities for a rapid diagnosis were regularly missed, notably for bone marrow samples, which could have been examined using staining methods complementary to those of the mycologist.